Mental Health of Adolescents in the Strawberry Generation: A Bibliometric Analysis - Nirmalawati, Trias; Qurniyawati, Eny (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Basic Health Research (2018) recorded that more than 31 million people aged 15 years and above experience mental health disorders, with more than 19 million experiencing emotional disorders and 12 million depression. Adolescent mental health is an important issue in psychosocial development, especially in the digital era. The Strawberry Generation, which refers to today's teenagers, faces social and digital pressures that can cause stress, anxiety, and depression. Aims: This study aims to assess global research trends in adolescent mental health for the strawberry generation based on the emergence of terms in text data. Methods: A literature review using bibliometric analysis is used to answer the research objectives. Results: This study uses the Google Scholar, Scopus, and PubMed databases to analyze research between 2019 and 2024; the result is 500 journal articles. Results show that in the last 5 years, the trend of adolescent mental health research has had good stability with minor fluctuations. A significant increase occurred in 2020, while 2021 showed a mild decrease. From 2022 to 2024, the number of articles remained relatively stable although there was a slight decrease in 2024 due to the data being collected in August 2024. This stability suggests that the topic continues to receive consistent attention over a long period. Conclusion: Bibliometric analysis highlights increased publications on social media's impact on adolescent mental health but notes limited research with a lack of longitudinal methods; digital platforms like survey apps can aid periodic data collection for deeper long-term studies.